Impurity diffusing composition, method for manufacturing semiconductor element and method for manufacturing solar cell using the same
The impurity diffusion composition, featuring polyvinyl alcohol with a specific saponification range, boric acid, and siloxane, addresses the issues of diffusivity and continuous printing performance, achieving uniform impurity diffusion and improved printing efficiency.
Patent Information
- Application Number
- JP2020551436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-26
- Filing Date
- 2020-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Existing impurity diffusion compositions for semiconductor substrates, particularly those using polyvinyl alcohol with a saponification level as described in Patent Document 1, suffer from insufficient diffusivity and challenges in continuous printing performance during screen printing.
An impurity diffusion composition comprising polyvinyl alcohol with a saponification degree of 20 mol % or more and less than 90 mol %, combined with boric acid as the impurity diffusion component and siloxane with specific partial structures, achieving a mass ratio of polyvinyl alcohol to siloxane of 30:70 to 75:25.
The composition enables uniform impurity diffusion into semiconductor substrates and excellent continuous printing performance during screen printing, improving diffusion properties and uniformity while maintaining solubility in organic solvents.
Smart Images

Figure 0007647100000007 
Figure 0007647100000008 
Figure 0007647100000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an impurity diffusing composition, a method for manufacturing a semiconductor device using the same, and a method for manufacturing a solar cell. [Background technology]
[0002] Currently, in the manufacture of solar cells, when a p-type or n-type impurity diffusion layer is formed in a semiconductor substrate, a method is adopted in which a diffusion source is formed on the substrate and impurities are diffused into the semiconductor substrate by thermal diffusion. For the formation of the diffusion source, a CVD method and a solution coating method using a liquid impurity diffusion composition are being considered. Among them, the solution coating method is preferably used because it does not require expensive equipment and is excellent in mass production.
[0003] When forming a p-type impurity diffusion layer by a solution coating method, a coating solution containing a boron compound and a hydroxyl-containing polymer compound such as polyvinyl alcohol is usually applied to the surface of a semiconductor substrate by spin coating or screen printing, and then thermally diffused. In such a coating solution, from the viewpoint of continuous printability during screen printing, a boron-containing diffusing composition using a polyhydric alcohol solvent and polyvinyl alcohol with a relatively low saponification degree of 50 to 90 mol % has been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-8953 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when polyvinyl alcohol having a saponification degree as described in Patent Document 1 is used, there is a problem that the diffusibility is insufficient.
[0006] The present invention has been made based on the above-mentioned circumstances, and an object of the present invention is to provide an impurity diffusing composition that enables uniform diffusion of impurities into a semiconductor substrate and excellent continuous printability during screen printing. [Means for solving the problem]
[0007] In order to solve the above problems, the impurity-diffusing composition of the present invention has the following configuration: That is, the present invention comprises (A) polyvinyl alcohol, (B) an impurity-diffusing component, and (C) a siloxane, and the saponification degree of the (A) polyvinyl alcohol is 20 mol % or more. 50 % by mole, (B) the impurity-diffusing component is boric acid; (C) The siloxane contains at least one of a partial structure represented by any one of the following general formulas (1) and (2) and a partial structure represented by any one of the following general formulas (3) and (4). The mass ratio of (A) polyvinyl alcohol to (C) siloxane (A):(C) is 30:70 to 75:25. It is an impurity-diffusing composition.
[0008] [ka]
[0009] (R 1 and R 2 each independently represents a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms; 1 and R 2 may be the same or different. 3 represents an aryl group having 6 to 15 carbon atoms, and 3 may be the same or different. 4 represents any one of a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, and an aryl group having 6 to 15 carbon atoms, and multiple R 4 may be the same or different.) Effect of the Invention
[0010] According to the present invention, it is possible to provide an impurity diffusing composition that enables uniform diffusion of impurities into a semiconductor substrate and excellent continuous printability during screen printing. [Brief description of the drawings]
[0011] [Figure 1] 1A to 1C are cross-sectional views showing process steps of a method for manufacturing a semiconductor element according to a first embodiment of the present invention. [Figure 2A] 5A to 5C are cross-sectional views showing process steps of a method for manufacturing a semiconductor device according to a second embodiment of the present invention. [Figure 2B] 5A to 5C are cross-sectional views showing the steps of a method for producing a back junction solar cell using a method for producing a semiconductor element according to a second embodiment of the present invention. [Figure 3A] 10A to 10C are cross-sectional views showing process steps of a method for manufacturing a semiconductor device according to a third embodiment of the present invention. [Figure 3B] 10A to 10C are cross-sectional views showing the steps of a method for producing a double-sided power generation solar cell using a method for producing a semiconductor element according to a third embodiment of the present invention. [Figure 4A] 10A to 10C are cross-sectional views showing process steps of a method for manufacturing a semiconductor device according to a fourth embodiment of the present invention. [Figure 4B] 10A to 10C are cross-sectional views showing the steps of a method for producing a double-sided power generation solar cell using a method for producing a semiconductor element according to a fourth embodiment of the present invention. [Diagram 5] 10A to 10C are cross-sectional views showing process steps of a manufacturing method of a semiconductor device according to a fifth embodiment of the present invention. [Figure 6] 1A to 1C are cross-sectional views showing a process for an example of a barrier property evaluation using an impurity diffusing composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, preferred embodiments of the impurity diffusion composition and the method for manufacturing a semiconductor device using the same according to the present invention will be described in detail with reference to the drawings as necessary. Note that the present invention is not limited to these embodiments.
[0013] The impurity-diffusing composition according to an embodiment of the present invention comprises (A) polyvinyl alcohol, (B) an impurity-diffusing component, and (C) a siloxane, in which the degree of saponification of the polyvinyl alcohol (A) is 20 mol % or more and less than 90 mol %, and the siloxane (C) comprises at least one of a partial structure represented by any one of the following general formulas (1) and (2) and a partial structure represented by any one of the following general formulas (3) and (4):
[0014] [ka]
[0015] R 1 and R 2 each independently represents a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms; 1 and R 2 may be the same or different. 3 represents an aryl group having 6 to 15 carbon atoms, and 3 may be the same or different. 4 represents any one of a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, and an aryl group having 6 to 15 carbon atoms, and multiple R 4 may be the same or different.
[0016] In this specification, the "impurity-diffusing composition" may be simply referred to as the "composition".
[0017] (A) Polyvinyl alcohol The impurity-diffusing composition according to the embodiment of the present invention contains (A) polyvinyl alcohol (hereinafter, may be simply referred to as "(A) PVA"). The saponification degree of (A) polyvinyl alcohol is 20 mol% or more and less than 90 mol%. By containing (A) polyvinyl alcohol, a complex is formed with (B) impurity-diffusing component, and a uniform coating can be formed when applied. By making the saponification degree of (A) polyvinyl alcohol 20% or more, the stability of the complex with (B) impurity-diffusing component is increased, and the diffusibility and diffusion uniformity are improved. In addition, by making the saponification degree of (A) polyvinyl alcohol less than 90%, the solubility in organic solvents is improved. From the viewpoint of improving storage stability, the saponification degree of (A) polyvinyl alcohol is preferably less than 70 mol%, more preferably less than 50 mol%. That is, by setting the degree of saponification of the (A) polyvinyl alcohol to be 20 mol % or more and less than 90 mol %, it is possible to provide an impurity diffusing composition which satisfies both solubility in organic solvents and complex stability, thereby enabling uniform diffusion of impurities into a semiconductor substrate and excellent continuous printability during screen printing.
[0018] The average degree of polymerization of the (A) polyvinyl alcohol is preferably 150 to 1000 in terms of solubility and complex stability. In the present invention, the average degree of polymerization and the degree of saponification are both values measured in accordance with JIS K 6726 (1994). The degree of saponification is a value measured by the back titration method among the methods described in the JIS.
[0019] From the viewpoints of achieving good thermal diffusion and suppressing organic residues on the substrate after removal of the composition, the content of (A) PVA is preferably 1 to 20 mass % and more preferably 5 to 15 mass % based on 100 mass % of the total composition.
[0020] (B) Impurity diffusion components The impurity diffusion composition according to the embodiment of the present invention contains an impurity diffusion component (B). By containing the impurity diffusion component (B), an impurity diffusion layer can be formed in a semiconductor substrate. The p-type impurity diffusion component is preferably a compound containing an element of group 13, and is preferably a boron compound. The n-type impurity diffusion component is preferably a compound containing an element of group 15, and is preferably a phosphorus compound.
[0021] Examples of the boron compound include boric acid, diboron trioxide, methylboronic acid, phenylboronic acid, trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, trioctyl borate, triphenyl borate, etc. Among these, from the viewpoint of doping properties, it is preferable that the (B) impurity-diffusing component is boric acid.
[0022] Examples of phosphorus compounds include phosphorus pentoxide, phosphoric acid, polyphosphoric acid, methyl phosphate, dimethyl phosphate, trimethyl phosphate, ethyl phosphate, diethyl phosphate, triethyl phosphate, propyl phosphate, dipropyl phosphate, tripropyl phosphate, butyl phosphate, dibutyl phosphate, tributyl phosphate, phenyl phosphate, diphenyl phosphate, triphenyl phosphate, and other phosphoric acid esters, and phosphorous acid esters such as methyl phosphite, dimethyl phosphite, trimethyl phosphite, ethyl phosphite, diethyl phosphite, triethyl phosphite, propyl phosphite, dipropyl phosphite, tripropyl phosphite, butyl phosphite, dibutyl phosphite, tributyl phosphite, phenyl phosphite, diphenyl phosphite, and triphenyl phosphite, and other phosphorous acid esters. Among these, phosphoric acid, diphosphorus pentoxide, and polyphosphoric acid are preferred from the viewpoint of doping properties.
[0023] The content of the (B) impurity-diffusing component in the impurity-diffusing composition can be determined arbitrarily depending on the resistance value required for the semiconductor substrate, but is preferably 0.1 to 10 mass % with respect to 100 mass % of the entire composition.
[0024] From the viewpoint of diffusion uniformity, the mass ratio (A):(B) of the (A) PVA to the (B) impurity-diffusing component is preferably 1:1 to 20:1, and more preferably 4:1 to 10:1.
[0025] (C) Siloxane The impurity-diffusing composition according to the embodiment of the present invention includes (C) siloxane, and (C) siloxane includes at least one of the partial structures represented by the following general formulas (1) and (2) and the partial structures represented by the above general formulas (3) and (4). The partial structures represented by general formulas (1) and (2) may be mixed or may be either one. The partial structures represented by general formulas (3) and (4) may be mixed or may be either one. By including (C) siloxane, the impurity-diffusing composition film can be densified. Also, the diffusibility of the (B) impurity-diffusing component can be improved.
[0026] In the impurity-diffusing composition, the mass ratio (A):(C) of (A) polyvinyl alcohol to (C) siloxane is preferably 30:70 to 75:25. By making the mass ratio of (A) PVA 30% or more, diffusibility is easily improved, and by making the mass ratio of (A) PVA 75% or less, the adhesiveness specific to PVA is easily suppressed, and sticking during screen printing is easily suppressed.
[0027] (C) The siloxane preferably contains 25 mol% or more of a partial structure represented by either of the general formulas (3) and (4) in terms of Si atoms. This prevents the crosslinking density between polysiloxane skeletons from becoming too high, and cracks are further suppressed even in a thick film. This makes it difficult for cracks to occur during the baking and thermal diffusion processes, thereby improving the stability of impurity diffusion. In addition, after thermal diffusion of impurities, the impurity diffusion layer can be used as a mask against other impurity diffusing agents. In order to have masking properties, it is better to have a large film thickness after diffusion, and the impurity diffusion composition of the present invention, which is difficult to crack even in a thick film, can be suitably used. In addition, even in a composition to which a thermal decomposition component such as a thickener is added, it is possible to fill the voids generated by thermal decomposition due to the reflow effect of the siloxane, and a dense film with few voids can be formed. Therefore, it is less susceptible to the atmosphere during diffusion, and high masking properties against other impurities can be obtained.
[0028] On the other hand, it is preferable that the siloxane contains a partial structure represented by either general formula (3) or (4) at 95 mol % or less in terms of Si atoms. This makes it possible to eliminate peeling residues after diffusion. The residues are thought to be carbides that remain after the organic matter has not been completely decomposed or volatilized, and not only do they hinder doping properties, but they also increase the contact resistance with the electrode to be formed later, causing a decrease in the efficiency of the solar cell.
[0029] From the viewpoint of further improving the crack resistance, masking property, and storage stability and reducing the influence of the diffusion atmosphere, the content of the partial structure represented by either of the general formulas (3) and (4) in the (C) siloxane is more preferably 35 mol % or more, and even more preferably 40 mol % or more. In addition, in order not to be influenced by the atmosphere or film thickness and not to generate residues, the content of the partial structure represented by either of the general formulas (3) and (4) is preferably 80 mol % or less. 1 , R 2 and R 4 When R is an alkyl group, the number of carbon atoms is set to 6 or less to suppress the generation of residues. 3 This makes it possible to fully utilize the reflow effect due to the aryl group.
[0030] R 3 The aryl group having 6 to 15 carbon atoms in the formula (I) may be either unsubstituted or substituted, and can be selected according to the properties of the composition. Specific examples of the aryl group having 6 to 15 carbon atoms include a phenyl group, a p-tolyl group, a m-tolyl group, an o-tolyl group, a p-hydroxyphenyl group, a p-styryl group, a p-methoxyphenyl group, and a naphthyl group, with the phenyl group, the p-tolyl group, and the m-tolyl group being particularly preferred.
[0031] R 1 , R 2 , R 4 The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 7 carbon atoms, the acyloxy group having 1 to 6 carbon atoms, the alkenyl group having 2 to 10 carbon atoms, and the aryl group having 6 to 15 carbon atoms in the above may be either unsubstituted or substituted, and can be selected depending on the properties of the composition.
[0032] Specific examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a t-butyl group, an n-hexyl group, a trifluoromethyl group, a 3,3,3-trifluoropropyl group, a 3-methoxy-n-propyl group, a glycidyl group, a 3-glycidoxypropyl group, a 3-aminopropyl group, a 3-mercaptopropyl group, and a 3-isocyanatopropyl group. From the viewpoint of residues, however, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and a t-butyl group having 4 carbon atoms or less are preferred.
[0033] Specific examples of the alkoxy group having 1 to 7 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, and a t-butoxy group.
[0034] Specific examples of alkenyl groups having 2 to 10 carbon atoms include vinyl groups, 1-propenyl groups, 1-butenyl groups, 2-methyl-1-propenyl groups, 1,3-butandienyl groups, 3-methoxy-1-propenyl groups, 3-acryloxypropyl groups, and 3-methacryloxypropyl groups. From the viewpoint of residues, however, vinyl groups, 1-propenyl groups, 1-butenyl groups, 2-methyl-1-propenyl groups, 1,3-butandienyl groups, and 3-methoxy-1-propenyl groups having 4 or less carbon atoms are particularly preferred.
[0035] Specific examples of the acyloxy group having 1 to 6 carbon atoms include an acetoxy group, a propionyloxy group, an acryloyloxy group, and a benzoyloxy group.
[0036] Specific examples of the aryl group having 6 to 15 carbon atoms include R 3 The same as those in
[0037] In order to form a denser and more crack-resistant film, R 2 and R 4 represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or an acyloxy group having 1 to 6 carbon atoms; R 1 It is preferable that represents an alkyl group having 1 to 4 carbon atoms or an alkenyl group having 2 to 4 carbon atoms. In other words, it is preferable that all of the constituent units of the polysiloxane are composed of trifunctional organosilanes.
[0038] It is also preferable that the 20% thermal decomposition temperature of the (C) siloxane is 550°C or higher. This allows the reflow effect of the (C) siloxane to be obtained after the organic components other than the (C) siloxane are completely removed by thermal decomposition, resulting in a denser film with less residue. Here, the 20% thermal decomposition temperature is the temperature at which the weight of the (C) siloxane decreases by 20% due to thermal decomposition. The thermal decomposition temperature can be measured using a thermogravimetric analyzer (TGA) or the like.
[0039] Specific examples of organosilanes that are the raw materials for the units of general formulae (3) and (4) include phenyltrimethoxysilane, phenyltriethoxysilane, p-hydroxyphenyltrimethoxysilane, p-tolyltrimethoxysilane, p-styryltrimethoxysilane, p-methoxyphenyltrimethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, 1-naphthyltrimethoxysilane, 2-naphthyltrimethoxysilane, 1-naphthyltriethoxysilane, and 2-naphthyltriethoxysilane. Among these, phenyltrimethoxysilane, p-tolyltrimethoxysilane, and p-methoxyphenyltrimethoxysilane are particularly preferred.
[0040] Specific examples of organosilanes that can be used as raw materials for the units of general formulas (1) and (2) include tetrafunctional silanes such as tetramethoxysilane, tetraethoxysilane, and tetraacetoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltriisopropoxysilane, ethyltri-n-butoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-butyltrimethoxysilane, and n-butyltriethoxysilane. Examples of the organosilanes include trifunctional silanes such as xysilane, glycidyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, trifluoromethyltrimethoxysilane, trifluoromethyltriethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-mercaptopropyltrimethoxysilane, and bifunctional silanes such as dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldiacetoxysilane, and di(n-butyl)dimethoxysilane. These organosilanes may be used alone or in combination of two or more. Among these organosilanes, trifunctional silanes are preferably used in terms of the denseness, crack resistance, residue, and curing speed of the film.
[0041] (C) Siloxane can be obtained, for example, by hydrolyzing an organosilane compound, and then condensing the hydrolyzate in the presence of a solvent or without a solvent. Various conditions for the hydrolysis reaction, such as acid concentration, reaction temperature, and reaction time, can be appropriately set in consideration of the reaction scale, the size and shape of the reaction vessel, and the like. For example, it is preferable to add an acid catalyst and water to the organosilane compound in a solvent over 1 to 180 minutes, and then react at room temperature to 110°C for 1 to 180 minutes. By carrying out the hydrolysis reaction under such conditions, it is possible to suppress a rapid reaction. The reaction temperature is more preferably 30 to 130°C.
[0042] The hydrolysis reaction is preferably carried out in the presence of an acid catalyst. Examples of the acid catalyst include inorganic hydrogen halide acids such as hydrochloric acid, hydrobromic acid, and hydroiodic acid, other inorganic acids such as sulfuric acid, nitric acid, phosphoric acid, hexafluorophosphoric acid, hexafluoroantimonic acid, boric acid, tetrafluoroboric acid, and chromic acid, sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid, and carboxylic acids such as acetic acid, citric acid, formic acid, gluconic acid, lactic acid, oxalic acid, tartaric acid, pyruvic acid, citric acid, succinic acid, fumaric acid, and malic acid. From the viewpoint of doping, the acid catalyst of the present invention is preferably free of atoms other than silicon, hydrogen, carbon, oxygen, nitrogen, and phosphorus as much as possible, and it is preferable to use an acid catalyst of phosphoric acid, formic acid, acetic acid, or carboxylic acid type.
[0043] The content of the acid catalyst is preferably 0.1 to 5 parts by weight based on 100 parts by weight of the total organosilane compounds used in the hydrolysis reaction. By setting the amount of the acid catalyst within the above range, the hydrolysis reaction can be easily controlled so that it proceeds as necessary and sufficiently.
[0044] The solvent used in the hydrolysis reaction of the organosilane compound and the condensation reaction of the hydrolysate is not particularly limited and can be appropriately selected in consideration of the stability, wettability, volatility, etc. of the resin composition. In addition, two or more types of solvents may be combined, or the reaction may be carried out without a solvent. Specific examples of the solvent include diethylene glycol methyl ethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, methyl lactate, ethyl lactate, diacetone alcohol, propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-1-butanol, dipropylene glycol monomethyl ether, dipropylene glycol-n-butyl ether, γ-butyrolactone, diethylene glycol monoethyl ether acetate, butyl diglycol acetate, ethyl acetoacetate, N-methyl-2-pyrrolidone, N,N-dimethylimidazolidinone, dipropylene glycol methyl ether acetate, 1,3-butylene glycol diacetate, diisobutyl ketone, propylene glycol t-butyl ether, propylene glycol n-butyl ether, etc. In addition to these, those described in paragraph 47 of International Publication No. 2015 / 002132 can be mentioned.
[0045] From the viewpoints of achieving good thermal diffusion and suppressing organic residues on the substrate after removal of the composition, the content of the (C) polysiloxane is preferably 1 to 30 mass % and more preferably 5 to 15 mass % with respect to 100 mass % of the total composition.
[0046] (D) Solvent The impurity-diffusing composition according to the embodiment of the present invention preferably further contains a solvent (D). The content of the solvent (D) is preferably 10 to 90 mass %, and more preferably 50 to 80 mass %, based on 100 mass % of the entire composition.
[0047] The (D) solvent can be used without any particular limitation, but from the viewpoint of further improving printability when using a screen printing method, a spin-coat printing method, etc., a solvent having a boiling point of 100° C. or higher is preferable. When the boiling point is 100° C. or higher, for example, when the impurity-diffusing composition is printed on a printing plate used in a screen printing method, the impurity-diffusing composition can be prevented from drying and adhering on the printing plate.
[0048] The content of the solvent having a boiling point of 100° C. or more is preferably 20% by weight or more based on the total amount of the solvent. Examples of the solvent having a boiling point of 100° C. or more include water (boiling point 100° C.), diethylene glycol methyl ethyl ether (boiling point 176° C.), ethylene glycol monoethyl ether acetate (boiling point 156.4° C.), ethylene glycol monomethyl ether acetate (boiling point 145° C.), methyl lactate (boiling point 145° C.), ethyl lactate (boiling point 155° C.), diacetone alcohol (boiling point 169° C.), propylene glycol monomethyl ether acetate (boiling point 145° C.), 3-methoxy-3-methyl-1-butanol (boiling point 174° C.), dipropylene glycol monomethyl ether (boiling point 188° C.), dipropylene glycol-n-butyl ether (boiling point 229° C.), γ-butyrolactone (boiling point 204° C.), diethylene glycol monoethyl ether Examples of the propylene glycol methyl ether acetate include butyl diglycol acetate (boiling point 217°C), butyl diglycol acetate (boiling point 246°C), ethyl acetoacetate (boiling point 181°C), N-methyl-2-pyrrolidone (boiling point 204°C), N,N-dimethylimidazolidinone (boiling point 226°C), dipropylene glycol methyl ether acetate (boiling point 213°C), 1,3-butylene glycol diacetate (boiling point 232°C), diisobutyl ketone (boiling point 168°C), propylene glycol t-butyl ether (boiling point 151°C), propylene glycol n-butyl ether (boiling point 170°C), acetylacetone (boiling point 140°C), diethylene glycol monobutyl ether (boiling point 171°C), and diethylene glycol monobutyl ether acetate (boiling point 245°C).
[0049] In addition, it is preferable that the (D) solvent contains a lactam solvent or a cyclic ester solvent. By containing a lactam solvent or a cyclic ester solvent, it becomes easier to suppress the increase in viscosity of the impurity-diffusing composition, and it also becomes easier to efficiently dissolve the (A) PVA. In addition, by containing a lactam solvent or a cyclic ester solvent, the stability of the complex of the (A) PVA and the (B) impurity-diffusing component is further improved. As a result, it becomes easier to suppress the phenomenon that the (A) PVA and the (B) impurity-diffusing component that have already formed a complex further react to form a three-dimensional complex, and it becomes easier to suppress the thickening of the impurity-diffusing composition over time and the generation of gel-like foreign matter due to the thickening. As a result, when the impurity-diffusing composition is used for coating, the coating film thickness tends to be uniform, and uniform impurity diffusion is also easily obtained in the subsequent impurity diffusion process.
[0050] Examples of lactam solvents include N-methyl-2-pyrrolidone, etc. Examples of cyclic ester solvents include β-propiolactone, β-butyrolactone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, γ-octalactone, γ-nonalactone, γ-decanolactone, δ-decanolactone, γ-undecalactone, δ-undecalactone, ω-undecalactone, ω-pentadecalactone, etc. These can be used alone or as a mixed solvent of two or more kinds.
[0051] The content of the lactam solvent or cyclic ester solvent contained in the impurity-diffusing composition is preferably 20% by mass or more, more preferably 50% by mass or more, of the solvent contained in the impurity-diffusing composition, in order to more effectively suppress the increase in viscosity in the impurity-diffusing composition. The upper limit of the content is not particularly limited, but is preferably 90% by mass or less, more preferably 80% by mass or less. Note that when the impurity-diffusing composition contains both a lactam solvent and a cyclic ester solvent, the content represents the total content of both.
[0052] In addition, since (A) PVA can be dissolved as an aqueous solution, (D) solvent may contain water. When (D) solvent contains water, the content of water in (D) solvent is preferably 0.1 to 10 mass %, more preferably 0.1 to 5 mass %, from the viewpoints of storage stability, screen continuous printability, and diffusibility of the solution.
[0053] (E) Thixotropic agent From the viewpoint of screen printing properties, the impurity diffusing composition according to the embodiment of the present invention preferably further contains (E) a thixotropic agent. Here, the thixotropic agent refers to a compound that imparts thixotropy to the impurity diffusing composition. In addition, imparting thixotropy means that the viscosity (η 1 ) and viscosity at high shear stress (η 2 ) ratio (η 1 / η 2 ) is increased. (E) By including a thixotropic agent, the pattern accuracy of screen printing can be further improved. This is for the following reasons. An impurity-diffusing composition containing a thixotropic agent has a low viscosity under high shear stress, so clogging of the screen is unlikely to occur during screen printing, and has a high viscosity under low shear stress, so bleeding immediately after printing and thickening of the pattern line width are unlikely to occur.
[0054] Specific examples of (E) thixotropic agents include cellulose, cellulose derivatives, sodium alginate, xanthan gum polysaccharides, gellan gum polysaccharides, guar gum polysaccharides, carrageenan polysaccharides, locust bean gum polysaccharides, carboxyvinyl polymers, hydrogenated castor oil, hydrogenated castor oil and fatty acid amide wax, special fatty acids, polyethylene oxide, mixtures of polyethylene oxide and amide, fatty acid polycarboxylic acids, phosphate ester surfactants, salts of long-chain polyaminoamide and phosphoric acid, special modified polyamides, bentonite, montmorillonite, magnesian montmorillonite, ferromontmorillonite, ferromagnesian montmorillonite, beidellite, aluminous beidellite, saponite, aluminous saponite, laponite, aluminum silicate, magnesium aluminum silicate, organic hectorite, fine particles of silicon oxide (fine silicon oxide particles), colloidal alumina, and calcium carbonate. From the viewpoint of compatibility with other components in the composition and reduction of residue, it is particularly preferable that the (E) thixotropic agent is a fine particle of silicon oxide. The thixotropic agent can be used alone, but it is also possible to combine two or more kinds of thixotropic agents. It is also more preferable to use it in combination with a thickener, as this can provide a higher effect.
[0055] The size of the fine particles is preferably a number average particle diameter of 5 nm or more and 500 nm or less. By setting the size in this range, it is possible to obtain a suitable intermolecular interaction and to impart high thixotropy. The size of the fine particles is preferably a number average particle diameter of 7 nm or more and 100 nm or less, and most preferably 10 nm or more and 30 nm or less.
[0056] The size of the fine particles in the present invention is measured by observation with a transmission electron microscope. The major axis of 10 randomly selected particles is measured, and the average of the measurements is taken as the number average particle size.
[0057] There is no limit to the viscosity of the impurity diffusing composition according to the embodiment of the present invention, and it can be appropriately changed depending on the printing method and film thickness. For example, in the case of a screen printing method, which is one of the preferred printing forms, the viscosity of the diffusing composition is preferably 5,000 mPa·s or more. This is because bleeding of the printed pattern can be suppressed and a good pattern can be obtained. A more preferred viscosity is 10,000 mPa·s or more. There is no particular upper limit, but from the viewpoint of storage stability and handling, a viscosity of 100,000 mPa·s or less is preferable.
[0058] Here, when the viscosity is less than 1,000 mPa s, it is the value measured at 20 rpm using an E-type digital viscometer in accordance with JIS Z 8803 (1991) "Solution viscosity - Measurement method", and when the viscosity is 1,000 mPa s or more, it is the value measured at 20 rpm using a B-type digital viscometer in accordance with JIS Z 8803 (1991) "Solution viscosity - Measurement method".
[0059] The thixotropy can be determined from the ratio of viscosities at different rotation speeds obtained by the above-mentioned viscosity measurement method. In the present invention, the viscosity at a rotation speed of 20 rpm (η 20 ) and viscosity at 2 rpm (η 2 ) ratio (η 2 / η 20 In order to form a pattern with high accuracy by screen printing, the thixotropy is preferably 2 or more, and more preferably 3 or more.
[0060] (F) Carboxylic Acid From the viewpoint of adjusting the pH of the composition, the impurity-diffusing composition according to the embodiment of the present invention preferably further contains (F) a carboxylic acid. Examples of the carboxylic acid include formic acid, acetic acid, and oxalic acid. Among them, it is more preferable that the (F) carboxylic acid is formic acid. From the viewpoint of the pH adjusting effect, the content of the (F) carboxylic acid is preferably 0.01 to 0.1 mass % in the entire composition.
[0061] (G) Surfactants The impurity-diffusing composition according to the embodiment of the present invention may contain a surfactant. By containing a surfactant, coating unevenness is improved and a more uniform coating film can be obtained. As the surfactant, a fluorine-based surfactant or a silicone-based surfactant is preferably used. When the surfactant is contained, the content of the surfactant in the impurity-diffusing composition is preferably 0.0001 to 1% by weight.
[0062] (H) Thickener The impurity diffusion composition according to the embodiment of the present invention may contain a thickener. This allows viscosity adjustment. In addition, the composition can be applied in a more precise pattern by a printing method such as screen printing. From the viewpoint of dense film formation and residue reduction, the thickener preferably has a 90% thermal decomposition temperature of 400° C. or less. The thickener is preferably polyethylene glycol, polyethylene oxide, polypropylene glycol, polypropylene oxide, or an acrylic acid ester resin, and among these, polyethylene oxide, polypropylene oxide, or an acrylic acid ester resin is preferable. From the viewpoint of storage stability, the thickener is particularly preferably an acrylic acid ester resin. Here, the 90% thermal decomposition temperature is the temperature at which the weight of the thickener is reduced by 90% due to thermal decomposition. The thermal decomposition temperature can be measured using a thermogravimetric analyzer (TGA) or the like.
[0063] The content of these thickeners in the impurity-diffusing composition is preferably 3% by weight or more and 20% by weight or less. By being in this range, a sufficient viscosity adjusting effect can be easily obtained, and at the same time, a denser film can be formed.
[0064] (pH) The impurity-diffusing composition according to the embodiment of the present invention preferably has a pH of 4.0 to 6.5. In this range, the complex between (A) PVA and (B) the impurity-diffusing component is more stabilized. In addition, even if the composition is used for diffusion after being stored for a certain period of time, the uniformity of the impurity diffusion concentration within the substrate surface is well maintained.
[0065] Methods for adjusting the pH include, but are not limited to, a method of adding an acid or a base to the composition, and a method of adjusting the pH when reducing impurities with an ion exchange resin as described below.
[0066] As the acid, inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as the above-mentioned (F) carboxylic acids are preferred.
[0067] The base is preferably an organic amine since it does not contain metal elements or halogens.
[0068] In particular, from the viewpoint of further improving storage stability, a method in which the addition of an organic amine is combined with the addition of formic acid, sulfuric acid, nitric acid, acetic acid or oxalic acid, or a method in which the addition of an organic amine is combined with adjustment using an ion exchange resin, is preferred.
[0069] Examples of organic amines include aromatic amines and aliphatic amines, among which aliphatic amines are preferred because they are highly basic and effective even when added in smaller amounts, and tertiary amines are more preferred from the viewpoint of suppressing side reactions with other components of the composition.
[0070] Specific examples of the aliphatic tertiary amine include, but are not limited to, trimethylamine, triethylamine, triisopropylamine, triisopropanolamine, triethanolamine, pyridine, piperazine, piperidine, pyrrolidine, ethylpiperidine, piperidineethanol, etc. Preferred are aliphatic cyclic tertiary amines such as piperazine, piperidine, pyrrolidine, ethylpiperidine, and piperidineethanol.
[0071] The content of the organic amine is preferably 0.01 to 2 mass % of the total composition, more preferably 0.02 to 0.5 mass %, and further preferably 0.03 to 0.1 mass % of the total composition.
[0072] The pH in the present invention is a value measured using a pH meter (LAQUA F-71, manufactured by Horiba, Ltd.). The pH is calibrated using the following five types of standard solutions (pH 2, 4, 7, 9, 12) as specified in JIS Z 8802 (2011) "pH measurement method". pH2 standard solution (oxalate) 0.05mol / L potassium tetraoxalate aqueous solution pH 4 standard solution (phthalate) 0.05mol / L potassium hydrogen phthalate aqueous solution pH 7 standard solution (neutral phosphate: a mixture of the following two aqueous solutions) 0.025mol / L potassium dihydrogen phosphate aqueous solution 0.025mol / L disodium hydrogen phosphate aqueous solution ○pH9 standard solution (borate) 0.01mol / L sodium tetraborate (borax) aqueous solution pH 12 standard solution Saturated calcium hydroxide solution.
[0073] The impurity-diffused composition according to the embodiment of the present invention preferably has a sodium (Na) content of 0.05 ppm or less. As a method for reducing Na, a method for purifying each component of the composition by recrystallization, distillation, column fractionation, ion exchange, etc. is used, but a method using an ion exchange resin is preferred.
[0074] Ion exchange can be performed by subjecting the entire composition containing the components (A) to (C) or at least one of the components (A) to (C) to an ion exchange treatment using an ion exchange resin. Since Na may be mixed in during the manufacturing process, it is most preferable to perform ion exchange at the end of the entire composition containing the components (A) to (C). Specific methods include, but are not limited to, passing the impurity-diffusing composition through a column packed with a cation exchange resin, adding a cation exchange resin to a liquid of the impurity-diffusing composition and stirring it, and removing the ion exchange resin after ion exchange.
[0075] In particular, when a cation exchange resin is used, the pH of the impurity-diffusing composition after ion exchange is less than 7, making it possible to reduce impurities and adjust the pH to the desired level at the same time.
[0076] As an ion exchange treatment method for adjusting the pH value to 4.0 to 6.5, a method of performing ion exchange treatment using a combination of a cation exchange resin and an anion exchange resin is preferable. Examples of the combination method include a method of appropriately mixing a cation exchange resin and an anion exchange resin, filling the mixture in a column, and passing the impurity-diffusing composition through the column, and a method of continuously passing the impurity-diffusing composition through a column filled with a cation exchange resin and a column filled with an anion exchange resin, but are not limited thereto.
[0077] (solid content concentration) The solid content of the impurity diffusion composition according to the embodiment of the present invention is not particularly limited, but is preferably in the range of 1% by mass or more and 90% by mass or less. If the solid content is lower than this range, the coating film thickness becomes too thin and it may be difficult to obtain the desired doping property and masking property. If the solid content is higher than this range, the storage stability may decrease.
[0078] <Method of manufacturing semiconductor device> A first embodiment of a method for manufacturing a semiconductor device of the present invention includes a step of applying an impurity diffusion composition of the present invention to a semiconductor substrate to form an impurity diffusion composition film, and a step of diffusing impurities from the impurity diffusion composition film to form an impurity diffusion layer on the semiconductor substrate.
[0079] Moreover, a second embodiment of the method for manufacturing a semiconductor device of the present invention includes a step of applying an n-type impurity diffusion composition to a semiconductor substrate to form an n-type impurity diffusion composition film, a step of applying the impurity diffusion composition of the present invention, which is a p-type impurity diffusion composition, to form an impurity diffusion composition film, and a step of heating the semiconductor substrate to simultaneously form an n-type impurity diffusion layer and a p-type impurity diffusion layer.
[0080] Furthermore, a third embodiment of the method for manufacturing a semiconductor device of the present invention includes a step of applying the impurity diffusion composition of the present invention, which is a p-type impurity diffusion composition, to one surface of a semiconductor substrate to form a p-type impurity diffusion composition film, a step of applying an n-type impurity diffusion composition to the other surface of the semiconductor substrate to form an n-type impurity diffusion composition film, and a step of heating the semiconductor substrate to simultaneously form a p-type impurity diffusion layer and an n-type impurity diffusion layer.
[0081] Furthermore, a fourth embodiment of the method for manufacturing a semiconductor device of the present invention includes a step of partially applying the impurity diffusion composition of the present invention, which is a p-type impurity diffusion composition, to one surface of a semiconductor substrate to form a first p-type impurity diffusion composition film, a step of applying a second p-type impurity diffusion composition to a portion where the first p-type impurity diffusion composition film is not formed to form a low-concentration p-type impurity diffusion composition film, a step of applying an n-type impurity diffusion composition to the other surface of the semiconductor substrate to form an n-type impurity diffusion composition film, and a step of simultaneously forming a high-concentration p-type impurity diffusion layer, a low-concentration p-type impurity diffusion layer, and an n-type impurity diffusion layer by heating the semiconductor substrate.
[0082] A fifth embodiment of the method for manufacturing a semiconductor element of the present invention is a method for manufacturing a semiconductor element using a plurality of semiconductor substrates, and includes the following steps (a) to (c), in which in steps (b) and (c), a pair of semiconductor substrates are arranged such that the surfaces on which the first conductivity type impurity diffusion composition film is formed face each other. (a) A step of applying the impurity diffusion composition of the present invention to one surface of each semiconductor substrate to form an impurity diffusion composition film of a first conductivity type. (b) A step of heating the semiconductor substrate on which the first conductivity type impurity diffusion composition film is formed, thereby diffusing the first conductivity type impurity into the semiconductor substrate to form a first conductivity type impurity diffusion layer. (c) heating the semiconductor substrate in an atmosphere having a gas containing an impurity of a second conductivity type to diffuse the impurity of the second conductivity type into the other surface of the semiconductor substrate, thereby forming an impurity diffusion layer of the second conductivity type.
[0083] Hereinafter, methods for forming an impurity diffusion layer that can be applied to the manufacturing method of these semiconductor devices will be described with reference to the drawings. Note that these are merely examples, and the methods that can be applied to the manufacturing method of the semiconductor device of the present invention are not limited to these.
[0084] (First embodiment) Fig. 1 shows an example of a first embodiment of the method for producing a semiconductor device of the present invention. First, as shown in Fig. 1(a), a p-type impurity diffusion composition film 12 is formed on a semiconductor substrate 11.
[0085] The semiconductor substrate may have an impurity concentration of, for example, 10 15 ~10 16 atoms / cm 3 Examples of the semiconductor substrate include n-type single crystal silicon, polycrystalline silicon, and crystalline silicon substrates mixed with other elements such as germanium and carbon. Semiconductors other than p-type crystalline silicon and silicon can also be used. The semiconductor substrate is preferably approximately rectangular with a thickness of 50 to 300 μm and an outer shape of 100 to 250 mm on each side. It is also preferable to etch the surface with a hydrofluoric acid solution or an alkaline solution. By etching, slice damage and natural oxide films can be removed.
[0086] A protective film may be formed on the light receiving surface of the semiconductor substrate. This protective film may be a known protective film such as silicon oxide or silicon nitride formed by a method such as CVD (chemical vapor deposition) or spin-on glass (SOG).
[0087] Examples of the method for applying the impurity diffusing composition include spin coating, screen printing, inkjet printing, slit coating, spray coating, letterpress printing, and intaglio printing.
[0088] After forming the coating film by these methods, it is preferable to dry the impurity-diffusing composition film for 30 seconds to 30 minutes at a temperature in the range of 50 to 200° C. using a hot plate, oven, etc. The thickness of the impurity-diffusing composition film after drying is preferably 100 nm or more from the viewpoint of impurity diffusibility, and is preferably 3 μm or less from the viewpoint of residue after etching.
[0089] Next, as shown in FIG. 1(b), impurities are diffused into the semiconductor substrate 11 to form a p-type impurity diffusion layer 13.
[0090] The impurity can be diffused by any known thermal diffusion method, such as electric heating, infrared heating, laser heating, or microwave heating.
[0091] The time and temperature of thermal diffusion can be appropriately set so as to obtain desired diffusion characteristics such as impurity diffusion concentration and diffusion depth. For example, by performing thermal diffusion at 800° C. or more and 1200° C. or less for 1 to 120 minutes, the surface impurity concentration can be reduced to 10 19 ~10 21 A diffusion layer of the above can be formed.
[0092] The diffusion atmosphere is not particularly limited, and may be air, or may be appropriately controlled by using an inert gas such as nitrogen or argon to control the amount of oxygen in the atmosphere. From the viewpoint of shortening the diffusion time, it is preferable to set the oxygen concentration in the atmosphere to 3% or less. Furthermore, if necessary, sintering may be performed at a temperature in the range of 200°C to 850°C before diffusion.
[0093] Next, as shown in FIG. 1(c), the p-type impurity diffusion composition film 12 formed on the surface of the semiconductor substrate 11 is removed.
[0094] As a removal method, for example, a known etching method can be used.
[0095] The material used for etching is not particularly limited, but preferably contains at least one of hydrogen fluoride, ammonium, phosphoric acid, sulfuric acid, and nitric acid as an etching component, and other components include water, an organic solvent, etc. Through the above process, a p-type impurity diffusion layer can be formed in the semiconductor substrate.
[0096] In the above example, a p-type impurity diffusion layer is formed using a p-type impurity diffusion composition film, but the present embodiment is not limited to this, and can naturally be applied to a case where an n-type impurity diffusion layer is formed using an n-type impurity diffusion composition film.
[0097] Next, a method for manufacturing a solar cell using the method for manufacturing a semiconductor element according to an example of the first embodiment of the present invention will be described with reference to (d) of Fig. 1. The solar cell obtained in this example of the embodiment is a single-sided power generation solar cell.
[0098] First, as shown in FIG. 1(d), a passivation layer 16 is formed on the front surface, and a passivation layer 17 is formed on the back surface.
[0099] The passivation layer may be made of a known material. These layers may be a single layer or multiple layers. For example, a thermal oxide layer, an aluminum oxide layer, a SiNx layer, and an amorphous silicon layer may be stacked.
[0100] An aluminum oxide layer is particularly preferred as the passivation layer on the side of the passivation layer 17, which also serves as an electrode.
[0101] These passivation layers can be formed by a deposition method such as a plasma CVD method or an ALD (atomic layer deposition) method, or by a coating method.
[0102] In one example of this embodiment, the passivation layer 16 is formed on a partial region of the light-receiving surface, and the passivation layer 17 is formed on the entire back surface.
[0103] Thereafter, as shown in FIG. 1(e), a contact electrode 18 is formed on the light-receiving surface in a portion where the passivation layer 16 is not present.
[0104] The electrodes can be formed by applying an electrode-forming paste and then subjecting it to a heat treatment.
[0105] In this way, a single-sided power generating solar cell 10 is obtained.
[0106] Second embodiment 2A shows an example of the second embodiment of the method for producing a semiconductor device of the present invention. First, as shown in (a) of FIG. 2A, an n-type impurity diffusion composition film 24 is patterned on a semiconductor substrate 21.
[0107] Examples of methods for forming the n-type impurity diffusion composition film include screen printing, inkjet printing, slit coating, spray coating, letterpress printing, and intaglio printing.
[0108] After forming a coating film by these methods, the n-type impurity diffusion composition film is preferably dried on a hot plate, in an oven, or the like at a temperature in the range of 50 to 200° C. for 30 seconds to 30 minutes.
[0109] The thickness of the n-type impurity diffusion composition film after drying is preferably 200 nm or more in consideration of masking properties against p-type impurities, and is preferably 5 μm or less in terms of crack resistance.
[0110] Next, as shown in FIG. 2A(b), a p-type impurity diffusion composition film 22 is formed using the n-type impurity diffusion composition film 24 as a mask.
[0111] In this case, as shown in (b) of FIG. 2A, the p-type impurity diffusion composition film may be formed on the entire surface, or may be formed only on the portion where the n-type impurity diffusion composition film is not present. Also, the p-type impurity diffusion composition may be applied so that a part of the p-type impurity diffusion composition overlaps the n-type impurity diffusion composition film.
[0112] Examples of the method for applying the p-type impurity diffusion composition include spin coating, screen printing, inkjet printing, slit coating, spray coating, letterpress printing, and intaglio printing.
[0113] After forming the coating film by these methods, the p-type impurity diffusion composition film is preferably dried for 30 seconds to 30 minutes at a temperature in the range of 50 to 200° C. using a hot plate, oven, etc. The thickness of the p-type impurity diffusion composition film after drying is preferably 100 nm or more from the viewpoint of the diffusibility of the p-type impurities, and is preferably 3 μm or less from the viewpoint of the residue after etching.
[0114] Next, as shown in (c) of FIG. 2A, the n-type impurity diffusion component in the n-type impurity diffusion composition film 24 and the p-type impurity diffusion component in the p-type impurity diffusion composition film 22 are simultaneously diffused into the semiconductor substrate 21 to form an n-type impurity diffusion layer 25 and a p-type impurity diffusion layer 23.
[0115] The method for applying, baking and diffusing the impurity diffusing composition may be the same as those described above.
[0116] Next, as shown in FIG. 2A(d), the n-type impurity diffusion composition film 24 and the p-type impurity diffusion composition film 22 formed on the surface of the semiconductor substrate 21 are removed.
[0117] As a removal method, for example, a known etching method can be used.
[0118] By the above steps, n-type and p-type impurity diffusion layers can be formed in the semiconductor substrate. By adopting such steps, the process can be further simplified compared to the conventional method.
[0119] Here, an example is shown in which the application of the n-type impurity diffusion composition is followed by the application of the p-type impurity diffusion composition, but it is also possible to apply the n-type impurity diffusion composition after the application of the p-type impurity diffusion composition. That is, it is also possible to apply the p-type impurity diffusion composition instead of the application of the n-type impurity diffusion composition in (a) of Fig. 2A, and to apply the n-type impurity diffusion composition instead of the application and diffusion of the p-type impurity diffusion composition in (b) of Fig. 2A.
[0120] In the second embodiment of the method for manufacturing a semiconductor device of the present invention, it is preferable to apply the p-type impurity diffusion composition after applying the n-type impurity diffusion composition.
[0121] Next, a method for manufacturing a solar cell using the method for manufacturing a semiconductor element according to an example of the second embodiment of the present invention will be described with reference to Fig. 2B. The solar cell obtained in this example of the embodiment is a back junction solar cell.
[0122] First, as shown in (e) of Fig. 2B, a protective film 26 is formed on the entire back surface of a semiconductor substrate 21 having an n-type impurity diffusion layer 25 and a p-type impurity diffusion layer 23 formed on the back surface. Next, as shown in (f) of Fig. 3, the protective film 26 is patterned by etching or the like to form a protective film opening 26a.
[0123] 2B(g), an electrode paste is pattern-applied in the area including the opening 26a by stripe application, screen printing, or the like, and then fired to form the n-type contact electrode 29 and the p-type contact electrode 28. In this way, the back junction solar cell 20 is obtained.
[0124] (Third embodiment) FIG. 3A shows an example of a third embodiment of the method for manufacturing a semiconductor device according to the present invention.
[0125] First, as shown in (a) of Fig. 3A, a p-type impurity diffusion composition film 32 is formed on a semiconductor substrate 31 using a p-type impurity diffusion composition of the present invention. Next, as shown in (b) of Fig. 3A, an n-type impurity diffusion composition film 34 is formed on the surface of the semiconductor substrate 31 opposite to the surface on which the p-type impurity diffusion composition film 32 is formed.
[0126] Next, as shown in FIG. 3A(c), the p-type impurity diffusion composition film 32 and the n-type impurity diffusion composition film 34 are simultaneously diffused into the semiconductor substrate 31 to form a p-type impurity diffusion layer 33 and an n-type impurity diffusion layer 35.
[0127] The method for applying, baking and diffusing the impurity diffusing composition may be the same as those described above.
[0128] Next, as shown in FIG. 3A(d), the p-type impurity diffusion composition film 32 and the n-type impurity diffusion composition film 34 formed on the surface of the semiconductor substrate 31 are removed.
[0129] As a removal method, for example, a known etching method can be used.
[0130] By the above steps, n-type and p-type impurity diffusion layers can be formed in the semiconductor substrate. By adopting such steps, the process can be simplified compared to the conventional method.
[0131] Here, an example is shown in which the n-type impurity diffusion composition is applied after the p-type impurity diffusion composition is applied, but it is also possible to apply the p-type impurity diffusion composition after the n-type impurity diffusion composition.
[0132] Next, a method for manufacturing a solar cell using the method for manufacturing a semiconductor element according to an example of the third embodiment of the present invention will be described with reference to Fig. 3B. The solar cell obtained in this example of the embodiment is a bifacial solar cell.
[0133] First, as shown in FIG. 3B(e), a passivation layer 36 and a passivation layer 37 are formed on the light-receiving surface and the back surface, respectively.
[0134] The materials used for the passivation layer, the layer configuration, and the formation method are the same as those in the first embodiment.
[0135] In one example of this embodiment, the passivation layer 36 and the passivation layer 37 are formed on a portion of the light-receiving surface and the back surface.
[0136] Thereafter, as shown in FIG. 3B(f), a p-type contact electrode 38 and an n-type contact electrode 39 are formed on the light-receiving surface and the back surface, respectively, in the portions where the passivation layers 36 and 37 are not present.
[0137] The electrodes can be formed by applying an electrode-forming paste and then subjecting it to a heat treatment.
[0138] In this way, a bifacial power generation solar cell 30 is obtained.
[0139] (Fourth embodiment) FIG. 4A shows an example of a fourth embodiment of the method for manufacturing a semiconductor device according to the present invention.
[0140] First, as shown in FIG. 4A(a), a high-concentration p-type impurity diffusion composition of the present invention is partially applied onto a semiconductor substrate 41 to form a high-concentration p-type impurity diffusion composition film .
[0141] Next, as shown in (b) of FIG. 4A, a low-concentration p-type impurity diffusion composition is applied to a portion of the semiconductor substrate 41 on which the high-concentration p-type impurity diffusion composition film 42 is not formed, thereby forming a low-concentration p-type impurity diffusion composition film 42′.
[0142] Next, as shown in FIG. 4A(c), an n-type impurity diffusion composition film 43 is formed on the other surface of the semiconductor substrate 41.
[0143] 4A(d), the high-concentration p-type impurity diffusion composition film 42, the low-concentration p-type impurity diffusion composition film 42', and the n-type impurity diffusion composition film 43 are simultaneously diffused into the semiconductor substrate 41 to form a high-concentration p-type impurity diffusion layer 44, a low-concentration p-type impurity diffusion layer 44', and an n-type impurity diffusion layer 45. Methods for applying, baking, and diffusing the impurity diffusion compositions include the same methods as those described above.
[0144] Next, as shown in (e) of FIG. 4A, the high concentration p-type impurity diffusion composition film 42, the low concentration p-type impurity diffusion composition film 42' and the n-type impurity diffusion composition film 43 formed on the surface of the semiconductor substrate 41 are removed.
[0145] As a removal method, for example, a known etching method can be used.
[0146] By the above steps, n-type and p-type impurity diffusion layers can be formed in the semiconductor substrate. By adopting such steps, the process can be simplified compared to the conventional method.
[0147] Here, an example is shown in which the n-type impurity diffusion composition is applied after the p-type impurity diffusion composition is applied, but it is also possible to apply the p-type impurity diffusion composition after the n-type impurity diffusion composition.
[0148] Further, although a paste coating method has been exemplified for forming the low concentration p-type impurity diffusion layer and n-type impurity diffusion layer, gas diffusion may also be used.
[0149] In addition, a high-concentration p-type impurity diffusion layer is one in which the p-type impurity concentration on the surface is 1×10 20 The above refers to a low-concentration impurity diffusion layer, where the p-type impurity concentration on the surface is 1×10 20 It refers to something less than.
[0150] Next, a method for manufacturing a solar cell using the method for manufacturing a semiconductor element according to an example of the fourth embodiment of the present invention will be described with reference to Fig. 4B. The solar cell obtained in this example of the embodiment is a bifacial solar cell.
[0151] First, as shown in (f) of Fig. 4B, a passivation layer 46 is formed on the light-receiving surface, and a passivation layer 47 is formed on the back surface. The materials used for the passivation layers, the layer configuration, and the formation method are the same as those in the first embodiment.
[0152] In one example of this embodiment, passivation layer 46 and passivation layer 47 are formed on a portion of the light-receiving surface and the back surface.
[0153] Thereafter, as shown in FIG. 4B(g), a p-type contact electrode 48 and an n-type contact electrode 49 are formed on the light-receiving surface and the back surface, respectively, in portions where the passivation layers 46 and 47 are not present.
[0154] The electrodes can be formed by applying an electrode-forming paste and then subjecting it to a heat treatment.
[0155] In this way, a bifacial power generation solar cell 40 is obtained.
[0156] Fifth embodiment FIG. 5 shows an example of a fifth embodiment of the method for manufacturing a semiconductor device according to the present invention.
[0157] ((a) process) As shown in FIG. 5(a), a first conductive type impurity diffusion composition is applied to one surface of a semiconductor substrate 51 to form a first conductive type impurity diffusion composition film 52.
[0158] In the following description, the first conductive type is p-type and the second conductive type is n-type. That is, the first conductive type impurity diffusion composition film is a p-type impurity diffusion composition film. Of course, the first conductive type and the second conductive type may be reversed.
[0159] 5A, the embodiment in which the p-type impurity diffusion composition is applied to the entire surface of one surface of the semiconductor substrate is described, but the p-type impurity diffusion composition may be applied to a part of the surface. The application method and firing method of the impurity diffusion composition may be the same as those described above.
[0160] ((b) process) As shown in FIG. 5(b)-1, two semiconductor substrates 51 each having a p-type impurity diffusion composition film 52 formed on one surface are placed on a diffusion board 110 with the surfaces on which the p-type impurity diffusion composition film 52 is formed facing each other.
[0161] The diffusion board has a groove for arranging the semiconductor substrate. There is no particular restriction on the size or pitch of the groove of the diffusion board. The diffusion board may be inclined with respect to the horizontal direction. There is no particular restriction on the material of the diffusion board as long as it can withstand the diffusion temperature, but quartz is preferable.
[0162] Next, as shown in FIG. 5(b-2), the diffusion board 110 on which the semiconductor substrate 51 is placed is heated in a diffusion furnace 100 to diffuse p-type impurities into the semiconductor substrate 51, thereby forming a p-type impurity diffusion layer 53.
[0163] In this case, since the pair of semiconductor substrates is arranged as described above, even if the p-type impurity diffuses from the p-type impurity diffusion composition film into the air, it is difficult for the p-type impurity to reach the surface of the semiconductor substrate opposite to the surface on which the p-type impurity diffusion composition film is formed. Therefore, it is possible to suppress the so-called out-diffusion, in which the impurity diffuses to a portion other than the intended portion in the semiconductor substrate. The same method as described above can be used as a method for diffusing the impurity diffusion composition.
[0164] In addition, prior to the step (b), it is preferable to heat-treat the semiconductor substrate having the p-type impurity diffusion composition film formed on one surface thereof at a temperature equal to or lower than the heat treatment temperature during diffusion and in an atmosphere containing oxygen to remove at least a part of the organic components such as the binder resin in the p-type impurity diffusion composition film. By removing at least a part of the organic components such as the binder resin in the p-type impurity diffusion composition film, the concentration of the impurity components in the p-type impurity diffusion composition film on the semiconductor substrate can be increased, and the diffusibility of the p-type impurity is likely to be improved.
[0165] ((c) process) In the step (c), the semiconductor substrate is heated while a gas containing an n-type impurity is being fed, thereby forming an n-type impurity diffusion layer 55 .
[0166] As a gas containing n-type impurities, POCl 3 Gases such as POCl 3 The gas is POCl 3 Add N to the solution 2 Bubbling with nitrogen / oxygen gas or POCl 3 It can be obtained by heating the solution. If the second conductivity type is p-type, BBr 3 , BCl 3 The following gases are included:
[0167] The heating temperature is preferably from 750°C to 1050°C, and more preferably from 800°C to 1000°C.
[0168] The gas atmosphere is not particularly limited, but is preferably a mixed gas atmosphere of nitrogen, oxygen, argon, helium, xenon, neon, krypton, etc., more preferably a mixed gas of nitrogen and oxygen, and particularly preferably a mixed gas of nitrogen and oxygen having an oxygen content of 5 volume % or less.
[0169] In addition, it is preferable to carry out the (c) step in the same gas atmosphere as in the (b) step, since this can shorten the process time for changing the gas atmosphere. In particular, it is preferable that the ratio of nitrogen to oxygen in the gas atmosphere in the (b) step is the same as that in the (c) step. In this case, the preferred ratio is oxygen:nitrogen=1:99 to 5:95 by volume.
[0170] After the step (b), a layer of the heat-treated p-type impurity diffusion composition film remains on the top of the p-type impurity diffusion layer. It is preferable to use this as a mask against gas containing n-type impurities in the step (c). This makes it possible to suppress the intrusion of n-type impurities into the p-type impurity diffusion layer.
[0171] Either step (b) or step (c) may be performed first, and step (c) can be performed simultaneously with step (b). When the heat-treated layer of the p-type impurity diffusion composition film is used as a mask, step (c) is preferably performed after step (b).
[0172] Furthermore, it is more preferable to carry out the step (c) continuously after the step (b). For example, it is preferable to move to the step (c) directly after the step (b) without removing the diffusion board from the firing furnace. "Carrying out the step (c) continuously after the step (b)" means carrying out the step (c) immediately after the step (b).
[0173] The heating temperature when forming the n-type impurity diffusion layer in the step (c) is preferably 50 to 200° C. lower than the heating temperature when forming the p-type impurity diffusion layer in the step (b). By setting the heating temperature when forming the n-type impurity diffusion layer in the step (c) to a temperature 50 to 200° C. lower than the heating temperature when forming the p-type impurity diffusion layer in the step (b), when the step (c) is performed consecutively after the step (b), the influence of heating on the p-type impurity diffusion layer formed in the step (b) can be minimized, making it easier to control the p-type impurity diffusion.
[0174] In step (c), since the heating temperature can be lower when diffusing with a gas containing n-type impurities than when diffusing with a gas containing p-type impurities, it is preferable that the first conductivity type is p-type and the second conductivity type is n-type.
[0175] <Method of manufacturing solar cell element> The method for manufacturing a solar cell of the present invention includes the method for manufacturing a semiconductor element of the present invention. Specifically, the method includes a step of forming an electrode on each impurity diffusion layer of the semiconductor substrate on which the first conductive type impurity diffusion layer and the second conductive type impurity diffusion layer are formed, which are obtained by the above-mentioned steps. For details, a single-sided power generation solar cell is shown in FIG. 1, a back junction type solar cell is shown in FIG. 2, and a double-sided power generation solar cell is shown in FIG. 3 and FIG. 4.
[0176] The semiconductor element manufacturing method and solar cell manufacturing method of the present invention are not limited to the above-described embodiments, and various modifications such as design changes may be made based on the knowledge of those skilled in the art, and such modified embodiments are also included in the scope of the present invention.
[0177] The impurity diffusing composition of the present invention can also be applied to photovoltaic elements such as solar cells, and semiconductor devices in which an impurity diffused region is patterned on the semiconductor surface, such as transistor arrays, diode arrays, photodiode arrays, and transducers. EXAMPLES
[0178] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Among the compounds used, those using abbreviations are shown below. GBL: gamma-butyrolactone PVA: Polyvinyl alcohol MeTMS: Methyltrimethoxysilane PhTMS: phenyltrimethoxysilane.
[0179] (1) Solution viscosity and storage stability The viscosity of the impurity-diffusing composition with a viscosity of less than 1,000 mPa·s was measured at a liquid temperature of 25°C and a rotation speed of 20 rpm using a rotational viscometer TVE-25L (E-type digital viscometer) manufactured by Toki Sangyo Co., Ltd. The viscosity of the impurity-diffusing composition with a viscosity of 1,000 mPa·s or more was measured at a liquid temperature of 25°C and a rotation speed of 20 rpm using a Brookfield RVDV-11+P (B-type digital viscometer). Here, the viscosity immediately after the preparation of the impurity-diffusing composition and the viscosity after storage at 25°C for 30 days after preparation were measured and used as an index of storage stability. The viscosity increase rate was judged to be 5% or less as excellent (A), 5% to 20% or less as good (B), 20% to 30% or less as acceptable (C), and more than 30% as bad (D).
[0180] (2) Peelability evaluation A 6-inch square textured n-type silicon wafer (Electronics and Materials Corporation, surface resistance 200 Ω□) was immersed in a 1% hydrofluoric acid solution for 1 minute, then rinsed with water, blown with air, and treated on a hot plate at 140°C for 5 minutes.
[0181] The impurity diffusion composition to be measured was applied to the silicon wafer by a known coating method so that the pre-baked film thickness was about 500 nm. After coating, the silicon wafer was pre-baked at 140° C. for 5 minutes.
[0182] Then, each silicon wafer was placed in an electric furnace and maintained at 900° C. for 30 minutes in an atmosphere of nitrogen:oxygen=99:1 (volume ratio) to thermally diffuse the impurities.
[0183] Each silicon wafer after thermal diffusion was immersed in a 5 wt% aqueous solution of hydrofluoric acid at 23°C for 1 minute to peel off the diffusing agent and mask. After peeling, the silicon wafer was immersed in pure water to wash, and the presence or absence of residue was visually observed on the surface. Those that could be visually confirmed to have surface deposits after immersion for 1 minute and could not be removed by rubbing with a cloth were rated worst (D), those that could be visually confirmed to have surface deposits after immersion for 1 minute but could be removed by rubbing with a cloth were rated bad (C), those that could not be visually confirmed to have surface deposits within 1 minute but more than 30 seconds were rated good (B), and those that could not be visually confirmed to have surface deposits within 30 seconds were rated excellent (A). From the viewpoint of production takt time, good (B) is acceptable, but excellent (A) is preferable.
[0184] (3) Sheet resistance measurement The silicon wafer after impurity diffusion used in the peelability evaluation was subjected to p / n determination using a p / n determination device, and the surface resistance was measured using a four-point probe surface resistance measurement device RT-70V (manufactured by Napson Co., Ltd.) to obtain the sheet resistance value. The sheet resistance value is an index of impurity diffusibility, and a smaller resistance value means a larger amount of impurity diffusion.
[0185] (4) Diffusion uniformity The surface concentration distribution of impurities was measured using a secondary ion mass spectrometer IMS7f (Camera) for the central part of the silicon wafer after impurity diffusion used in the sheet resistance measurement. From the obtained surface concentration distribution, the surface concentration was read at 10 points at 100 μm intervals, and the ratio of the average to the standard deviation, "standard deviation / average," was calculated. "Standard deviation / average" of 0.3 or less was judged as excellent (A), that between 0.3 and 0.6 or less was good (B), that between 0.6 and 0.9 or less was not bad (C), and that above 0.9 was bad (D). Since the variation in the surface concentration of impurities has a large effect on the power generation efficiency, it is most preferable that it is excellent (A).
[0186] (5) Barrier properties An n-type silicon wafer (manufactured by Ferrotec Silicon Corporation, surface resistivity 410 Ω / □) cut to 3 cm x 3 cm was immersed in a 1% hydrofluoric acid solution for 1 minute, then washed with water, blown with air, and treated on a hot plate at 140°C for 5 minutes.
[0187] 6(a), the p-type impurity diffusion composition of each Example and Comparative Example was applied to the silicon wafer 61 by a known application method so that the pre-baked film thickness was about 500 nm. After application, the silicon wafer was pre-baked at 140° C. for 5 minutes to prepare a p-type impurity diffusion composition film 62.
[0188] 6(b), an n-type impurity diffusing composition (OCD T-1, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied to another silicon wafer 63 by a known application method so that the pre-baked film thickness was about 500 nm. After application, the silicon wafer was pre-baked at 140° C. for 5 minutes to prepare an n-type impurity diffusing composition coating film 64.
[0189] 6(c), the silicon wafer 61 on which the p-type impurity diffusion composition film 62 was formed and the silicon wafer 63 on which the n-type impurity diffusion composition film 64 was formed were placed in an electric furnace with a gap of 5 mm between them, and the impurities were thermally diffused by maintaining the temperature at 900°C for 30 minutes in an atmosphere of nitrogen:oxygen=99:1 (volume ratio). As a result, a p-type impurity diffusion layer 65 was formed in the silicon wafer 61, and an n-type impurity diffusion layer 66 was formed in the silicon wafer 63, as shown in FIG. 6(d).
[0190] After thermal diffusion, each silicon wafer was immersed in a 5 wt % aqueous solution of hydrofluoric acid at 23°C for 1 minute to peel off the hardened diffusing agent (Figure 6(e)).
[0191] Thereafter, the surface concentration distribution of phosphorus element was measured for the silicon wafer 61 using a secondary ion mass spectrometer IMS7f (manufactured by Camera Corporation). A lower surface concentration of phosphorus element means a higher barrier property against phosphorus element diffusing from the opposing n-type impurity diffusion composition. 17The following are excellent (A), 10 17 Exceeding 10 18 The following are good (B), 10 18 Exceeding 10 19 The following are not bad (C), 10 19 Anything above this was judged as bad (D).
[0192] In the case of an n-type impurity diffusion composition, the measurement is carried out as follows. An n-type silicon wafer (manufactured by Ferrotec Silicon Corporation, surface resistivity 410 Ω / □) cut to 3 cm x 3 cm was immersed in a 1% hydrofluoric acid solution for 1 minute, then washed with water, blown with air, and treated on a hot plate at 140°C for 5 minutes.
[0193] 6(a), a p-type impurity diffusion composition (manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied to the silicon wafer 61 by a known application method so that the pre-baked film thickness was about 500 nm. After application, the silicon wafer was pre-baked at 140° C. for 5 minutes to prepare a p-type impurity diffusion composition film 62.
[0194] 6(b), the n-type impurity diffusing composition of the present invention was applied to another silicon wafer 63 by a known application method so that the pre-baked film thickness was about 500 nm. After application, the silicon wafer was pre-baked at 140° C. for 5 minutes to prepare an n-type impurity diffusing composition coating film 64.
[0195] 6(c), the silicon wafer 61 on which the p-type impurity diffusion composition film 62 was formed and the silicon wafer 63 on which the n-type impurity diffusion composition film 64 was formed were placed in an electric furnace with a gap of 5 mm between them, and the impurities were thermally diffused by maintaining the temperature at 900°C for 30 minutes in an atmosphere of nitrogen:oxygen=99:1 (volume ratio). As a result, a p-type impurity diffusion layer 65 was formed in the silicon wafer 61, and an n-type impurity diffusion layer 66 was formed in the silicon wafer 63, as shown in FIG. 6(d).
[0196] After thermal diffusion, each silicon wafer was immersed in a 5 wt % aqueous solution of hydrofluoric acid at 23°C for 1 minute to peel off the hardened diffusing agent (Figure 6(e)).
[0197] Thereafter, the surface concentration distribution of boron element was measured for the silicon wafer 63 using a secondary ion mass spectrometer IMS7f (manufactured by Camera Corporation). A lower surface concentration of boron element means a higher barrier property against boron element diffusing from the opposing p-type impurity diffusion composition. 17 The following are excellent (A), 10 17 Exceeding 10 18 The following are good (B), 10 18 Exceeding 10 19 The following are not bad (C), 10 19 Anything above this was judged as bad (D).
[0198] (6) Screen printability The impurity diffusion compositions of the respective Examples and Comparative Examples were patterned into stripes by screen printing, and the precision of the stripe width was confirmed.
[0199] A semiconductor substrate made of n-type single crystal silicon with a side length of 156 mm was prepared, and both surfaces were alkaline etched to remove slice damage and natural oxides. During this process, numerous projections and recesses, typically with a width of 40 to 100 μm and a depth of 3 to 4 μm, were formed on both sides of the semiconductor substrate, and this was used as the coating substrate.
[0200] A screen printing machine (Microtec Corporation, TM-750 model) was used to form a striped pattern using a screen mask (SUS Corporation, 400 mesh, line diameter 23 μm) with 175 openings, each 200 μm wide and 13.5 cm long, with a pitch of 600 μm.
[0201] After screen printing the p-type impurity diffusion composition, the substrate was heated in air at 140°C for 5 minutes and then at 230°C for 30 minutes to form a pattern with a thickness of approximately 1.5 μm, a width of approximately 210 μm, a pitch of 600 μm, and a length of 13.5 cm.
[0202] Here, the line width was measured at 10 equally spaced points on any one line, and those with a standard deviation of the coating width within 12.5 μm were judged as excellent (A), those with a standard deviation of more than 12.5 μm and less than 15 μm were judged as good (B), those with a standard deviation of more than 15 μm and less than 17.5 μm were judged as not bad (C), and those with a standard deviation of more than 17.5 μm and less than 20 μm were judged as bad (D).
[0203] (7) Continuous screen printing The screen printability evaluation was performed on 1,000 sheets in succession without any coating defects such as bleeding or smearing, and was judged as excellent (A). The screen printability evaluation was performed on 100 to 999 sheets in succession with coating defects such as bleeding or smearing occurring, and was judged as good (B). The screen printability evaluation was performed on 10 to 99 sheets in succession with coating defects such as bleeding or smearing occurring, and was judged as not bad (C). The screen printability evaluation was performed on 10 sheets in succession with coating defects such as bleeding or smearing occurring, and was judged as bad (D).
[0204] (8) Sticking The screen printability evaluation was performed on 1,000 sheets in succession without sticking, and was judged as excellent (A); the screen printability evaluation was performed on 100 to 999 sheets in succession with sticking, and was judged as good (B); the screen printability evaluation was performed on 10 to 99 sheets in succession with sticking, and was judged as not bad (C); and the screen printability evaluation was performed on 10 sheets in succession with sticking, and was judged as bad (D). In addition, Examples 5, 6, 8, 9, and 11 ~17 , 19 are reference examples 5, 6, 8, 9, and 11, respectively. ~17 , read as 19.
[0205] Reference example 1 (1) Synthesis of polysiloxane solution A A 1000mL three-neck flask was charged with 183.25g of KBM-13 (methyltrimethoxysilane), 266.75g of KBM-103 (phenyltrimethoxysilane), and 403.36g of GBL, and an aqueous solution of formic acid in which 0.45g of formic acid was dissolved in 145.29g of water was added over 30 minutes while stirring at 40°C. After the dropwise addition, the mixture was stirred at 40°C for 1 hour, then heated to 70°C and stirred for 30 minutes. The oil bath was then heated to 115°C. One hour after the start of the temperature increase, the internal temperature of the solution reached 100°C, and the mixture was heated and stirred for 1 hour (internal temperature was 100-110°C). The resulting solution was cooled in an ice bath to obtain polysiloxane solution A (PhTMS(50) / MeTMS(50)). The solids concentration of the polysiloxane solution A was 39.0 mass %, and the weight average molecular weight (Mw) was 2,500.
[0206] (2) Preparation of impurity-diffusing composition 1 13.42 g of the polysiloxane solution A synthesized above, 1.31 g of boric acid, 11.63 g of polyvinyl alcohol with a saponification degree of 89 mol% (manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.) (hereinafter referred to as polyvinyl alcohol (89)), 3.9 g of Aerosil VPNKC130 (manufactured by Nippon Aerosil Co., Ltd.) which is fine silicon oxide particles, 24.64 g of GBL, 35.1 g of terpineol, and 10 g of water were mixed and thoroughly stirred to be homogenous. Here, the amount of formic acid carried over from polysiloxane solution A was 0.006 mass%. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0207] Reference example 2 Except for the degree of saponification of polyvinyl alcohol being 70 mol%, Reference example An impurity-diffusing composition 2 was obtained in the same manner as in 1. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0208] Reference example 3 Except for the degree of saponification of polyvinyl alcohol being 69 mol%, Reference example Impurity-diffusing composition 3 was obtained in the same manner as in 1. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0209] Reference example 4 Except for the degree of saponification of polyvinyl alcohol being 50 mol %, Reference example An impurity-diffusing composition 4 was obtained in the same manner as in 1. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0210] Example 5 Except for the saponification degree of polyvinyl alcohol being 49 mol%, Reference example Impurity-diffusing composition 5 was obtained in the same manner as in 1. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0211] Example 6 Except for the degree of saponification of polyvinyl alcohol being 20 mol%, Reference example Impurity-diffusing composition 6 was obtained in the same manner as in 1. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0212] Reference example 7 An impurity-diffusing composition 7 was obtained in the same manner as in Example 5, except that the mass ratio (A):(C) of (A) polyvinyl alcohol and (C) siloxane was set to 20:80. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0213] Example 8 An impurity-diffusing composition 8 was obtained in the same manner as in Example 5, except that the mass ratio (A):(C) of (A) polyvinyl alcohol and (C) siloxane was set to 30:70. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0214] Example 9 An impurity-diffusing composition 9 was obtained in the same manner as in Example 5, except that the mass ratio (A):(C) of (A) polyvinyl alcohol and (C) siloxane was set to 75:25. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0215] Reference example 10 An impurity-diffusing composition 10 was obtained in the same manner as in Example 5, except that the mass ratio (A):(C) of (A) polyvinyl alcohol and (C) siloxane was set to 80:20. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0216] Example 11 Except for changing the solvent from GBL to N-methyl-2-pyrrolidone, the procedure was the same as in Example 5 to obtain an impurity-diffusing composition 11. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0217] Example 12 Except for the amount of water being 5.0g, Example 5 In the same manner as above, impurity-diffusing composition 12 was obtained. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0218] Example 13 Other than the amount of water being 2.5g, Example 5 In the same manner as above, impurity-diffusing composition 13 was obtained. As shown in Table 2, the evaluation results of the obtained solution were all good.
[0219] Example 14 0.004 g of formic acid was added to the impurity-diffusing composition 5 so that the amount of formic acid in the composition was 0.01 mass %, thereby preparing an impurity-diffusing composition 14. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0220] Example 15 0.094 g of formic acid was added to the impurity-diffusing composition 5 so that the amount of formic acid in the composition was 0.1 mass % to prepare an impurity-diffusing composition 15. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0221] Example 16 The impurity-diffusing composition 5 was subjected to treatment (X) with an ion exchange resin to prepare an impurity-diffusing composition 16. The evaluation results of the obtained solution were all good, as shown in Table 2. Here, the treatment (X) with an ion exchange resin refers to the following treatment. (X) The resulting solution is passed through a column packed with a cation exchange resin (Amberlyst 15JS-HG-DRY, manufactured by Organo Corporation).
[0222] Example 17 The impurity-diffusing composition 5 was subjected to treatment (Y) with an ion exchange resin to prepare an impurity-diffusing composition 17. The evaluation results of the obtained solution were all good, as shown in Table 2. Here, the treatment (Y) with an ion exchange resin refers to the following treatment. (Y) The resulting solution is passed through a column packed with a mixed cation and anion exchange resin (Amberlyst MSPS2-1-DRY, manufactured by Organo Corporation).
[0223] Example 18 0.004 g of formic acid was added to the impurity-diffusing composition 13 so that the amount of formic acid in the composition was 0.01 mass %, thereby preparing the impurity-diffusing composition 18. The evaluation results of the obtained solution were all good, as shown in Table 2.
[0224] Example 19 Except for omitting the fine particle silicon oxide, the procedure was the same as in Example 5 to obtain an impurity-diffusing composition 19. The evaluation results of the obtained solution were as shown in Table 2.
[0225] Reference example 20 Except for using trimethyl borate instead of boric acid, an impurity-diffusing composition 20 was obtained in the same manner as in Example 5. The evaluation results of the obtained solution were as shown in Table 2.
[0226] Comparative Example 1 Except for changing the degree of saponification of polyvinyl alcohol to 90 mol %, an impurity-diffusing composition 21 was obtained in the same manner as in Example 1. As shown in Table 2, the evaluation result of the obtained solution showed that the screen continuous printability was poor.
[0227] Comparative Example 2 Except for changing the degree of saponification of polyvinyl alcohol to 10 mol %, an impurity-diffusing composition 22 was obtained in the same manner as in Example 1. As shown in Table 2, the evaluation result of the obtained solution showed poor diffusion uniformity.
[0228] Comparative Example 3 An impurity-diffusing composition 23 was obtained in the same manner as in Example 5, except that (MeTMS(100) / PhTMS(0)) was used. As shown in Table 2, the evaluation results of the obtained solution showed poor diffusion uniformity.
[0229] Comparative Example 4 Except for using (MeTMS(0) / PhTMS(100)), the procedure of Example 5 was repeated to obtain an impurity-diffusing composition 24. As shown in Table 2, the evaluation results of the obtained solution showed poor diffusion uniformity.
[0230] [Table 1-1]
[0231] [Table 1-2]
[0232] [Table 2] [Explanation of symbols]
[0233] 10, 20, 30, 40 solar cells 11, 21, 31, 41, 51, 61, 63 Semiconductor substrate 12, 22, 32, 42, 42', 52, 62 p-type impurity diffusion composition film 13, 23, 33, 44, 44', 53 p-type impurity diffusion layer 24, 34, 43, 64 n-type impurity diffusion composite film 25, 35, 45, 55, 66 n-type impurity diffusion layer 16, 17, 26, 36, 37, 46, 47 Passivation layer 18, 28, 29, 38, 39, 48, 49 Contact electrodes 26 Protective film 26a aperture 100 Diffusion furnace 110 Diffusion Board
Claims
1. a polyvinyl alcohol (A), an impurity-diffusing component (B), and a siloxane (C), wherein the degree of saponification of the polyvinyl alcohol (A) is 20 mol % or more and less than 50 mol %, the impurity-diffusing component (B) is boric acid, the siloxane (C) contains at least one partial structure represented by any one of the following general formulas (1) and (2) and at least one partial structure represented by any one of the following general formulas (3) and (4), a mass ratio of the polyvinyl alcohol (A) to the siloxane (C) (A):(C) is 30:70 to 75:25, and the pH is 4.0 to 6.5, The impurity-diffusing composition further comprises a solvent (D), the water content of the solvent (D) being 0.1 to 5 mass %. 【Chemistry 1】 (R 1 and R 2 each independently represents a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms; 1 and R 2 may be the same or different. 3 represents an aryl group having 6 to 15 carbon atoms, 3 may be the same or different. 4 represents any one of a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, and an aryl group having 6 to 15 carbon atoms; 4 may be the same or different.)
2. 2. The impurity-diffusing composition according to claim 1, wherein the solvent (D) contains a lactam solvent or a cyclic ester solvent, and the content of the lactam solvent or the cyclic ester solvent in the solvent (D) is 20 mass % or more.
3. 3. The impurity-diffusing composition according to claim 1, further comprising (E) a thixotropic agent, the (E) thixotropic agent being fine particles of silicon oxide.
4. 4. The impurity-diffusing composition according to claim 1, further comprising: (F) 0.01 to 0.1 mass % of a carboxylic acid.
5. 5. The impurity-diffusing composition according to claim 4, wherein the carboxylic acid (F) is formic acid.
6. A method for manufacturing a semiconductor device, comprising the steps of: applying the impurity diffusion composition according to any one of claims 1 to 5 to a semiconductor substrate to form an impurity diffusion composition film; and diffusing impurities from the impurity diffusion composition film to form an impurity diffusion layer on the semiconductor substrate.
7. A method for manufacturing a semiconductor device, comprising the steps of: applying an n-type impurity diffusion composition to a semiconductor substrate to form an n-type impurity diffusion composition film; applying an impurity diffusion composition according to any one of claims 1 to 5, which is a p-type impurity diffusion composition, to form an impurity diffusion composition film; and heating the semiconductor substrate to simultaneously form an n-type impurity diffusion layer and a p-type impurity diffusion layer.
8. A method for manufacturing a semiconductor device, comprising the steps of: applying the impurity diffusion composition according to any one of claims 1 to 5, which is a p-type impurity diffusion composition, to one surface of a semiconductor substrate to form a p-type impurity diffusion composition film; applying an n-type impurity diffusion composition to the other surface of the semiconductor substrate to form an n-type impurity diffusion composition film; and heating the semiconductor substrate to simultaneously form a p-type impurity diffusion layer and an n-type impurity diffusion layer.
9. A method for manufacturing a semiconductor device, comprising the steps of: partially coating one surface of a semiconductor substrate with the impurity diffusion composition according to any one of claims 1 to 5, which is a p-type impurity diffusion composition, to form a first p-type impurity diffusion composition film; coating a second p-type impurity diffusion composition on a portion where the first p-type impurity diffusion composition film is not formed, to form a low-concentration p-type impurity diffusion composition film; coating the other surface of the semiconductor substrate with an n-type impurity diffusion composition to form an n-type impurity diffusion composition film; and heating the semiconductor substrate to simultaneously form a high-concentration p-type impurity diffusion layer, a low-concentration p-type impurity diffusion layer, and an n-type impurity diffusion layer.
10. A method for manufacturing a semiconductor device using a plurality of semiconductor substrates, comprising the steps of (a) to (c) below, in which in steps (b) and (c), a pair of semiconductor substrates are arranged such that their surfaces on which a first conductivity type impurity diffusion composition film is formed face each other. (a) A step of applying the impurity diffusion composition according to any one of claims 1 to 5 onto one surface of each semiconductor substrate to form an impurity diffusion composition film of a first conductivity type. (b) A step of heating the semiconductor substrate on which the first conductivity type impurity diffusion composition film is formed to diffuse the first conductivity type impurity into the semiconductor substrate, thereby forming a first conductivity type impurity diffusion layer. (c) heating the semiconductor substrate in an atmosphere having a gas containing an impurity of a second conductivity type to diffuse the impurity of the second conductivity type into the other surface of the semiconductor substrate, thereby forming an impurity diffusion layer of the second conductivity type.
11. A method for manufacturing a solar cell, comprising the method for manufacturing a semiconductor element according to any one of claims 6 to 10.
Citation Information
Patent Citations
Solar cell manufacturing method, solar cell and semiconductor device manufacturing method
JP2006310373A
Coating liquid for diffusing phosphor
JP2010062334A
Coating liquid for diffusing impurity
JP2013008953A
Coating liquid for p-type diffusion layer
JP2013153052A
Coating liquid for dopant diffusion, method for applying the same, method for manufacturing semiconductor using the same, and semiconductor
JP2014030011A